Preferential trade agreements and international law - Graeme Baber. (Routledge, 2024)
This book considers the structure of the World Trade Organization’s agreements and the types of preferential trade arrangements, and deliberates the value of the latter in the light of the operation of the former. Preferential Trade Agreements and International Law offers a comprehensive examination of preferential trade agreements and considers the features of specific regional and bilateral trade agreements without drawing upon systematic features and trends.